ANALYSIS OF THE USE OF AUGMENTED REALITY IN LEARNING MATHEMATICS - Warsito Warsito; Fatihah Nanda Kuncara; Bara P. Pradja (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
The use of textbooks or LKPD as learning media has several limitations, such as students' difficulties in reading and understanding content and a lack of interactivity, which may lead to boredom during the learning process. One promising technological solution to address these challenges is Augmented Reality (AR). This study aims to identify the common mathematical topics, learning models, and objectives frequently examined in research on AR-based mathematics education. The research methodology employed is a literature study, analyzing previous studies related to the integration of AR in mathematics learning. The findings indicate that the most frequently studied mathematical topic in AR-based research is geometry, particularly three-dimensional (3D) shapes, as AR allows students to observe and interact with geometric models more realistically. Additionally, the most commonly implemented learning models in AR-based mathematics education include inquiry-based learning and game-based learning. The impact of AR in mathematics learning includes enhancing student interest and motivation, deepening conceptual understanding, and increasing student engagement in the learning process.